Planning for teaching in the teaching-learning process: Translation and Law - Gregorio Cano, Ana; Casas Agudo, Daniel (Historia y Comunicación Social, 2014)
This article shows a practical proposal for a study guide for Financial and Tax Law and Translation and Interpreting students. Some key aspects both from the student and the professor perspectives and the necessary criteria in order to achieve the greatest success will be explained and clarified. Furthermore, the basis for a transparent, clear and quality assessment will be highlighted.
Keywords: Study guide; teaching guide; Translation; Financial and Tax Law; teaching and learning process.